The The important role of cold atmospheric plasma in wounds healing: Cold atmospheric plasma - Riyam Adnan; Yamam Adnan Hammudi; Saeed Ghnaimawi (Institute of Computer Science (IOCS), 2024)
Cold plasma is the fourth state of matter it can be generated using different types of gases like argon or helium or other gases by applying electrical field to get plasma with a temperature lower than 40degree so it's considered safe to be used in human without affecting the normal body cells. Recently cold plasma came to be known as one of the most important technologies in medicine and pharmaceutical sciences. In this study we will be focusing on discussing wounds, wounds healing, different methods that help in wound care and the important role of cold plasma in accelerating the wound healing process by reviewing all the recent studies in this subject to offer a full understanding, this study showed the cold plasma has the ability to improve and accelerate wounds healing through specific mechanisms which help in cell migration and proliferation in addition to increase the vascularization at the wound side and help in gathering the fibroblasts and keratinocytes and the production of reactive nitrogen and oxygen species (RNS,ROS) and this encourages the future researches and in-vevo studies to prove its efficiency in other medical fields and make use of its many effects like antiseptic, antimicrobial, anti-tumor and also its many application in dental field like endodontic treatment, antibacterial in dental caries and implants.